2016
DOI: 10.1021/acs.analchem.6b02674
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Optical-Filter Detection System for Discrimination of Infrared Chemical Signatures

Abstract: Optical-filter-based chemical sensors have the potential to dramatically alter the field of hazardous materials sensing. Such devices could be constructed using inexpensive components, in a small and lightweight package, for sensing hazardous chemicals in defense, industrial, and environmental applications. Filter-based sensors can be designed to mimic human color vision. Recent developments in this field have used this approach to discriminate between strongly overlapping chemical signatures in the mid-infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This system was based off a similar approach to that previously reported in the literature for discrimination of different gas phase chemicals. 18,19 A significant difference between previously reported results and the current work is that this work is focused on evaluating the capability of the human-color vision-based IR filter approach to discriminate between different solid explosives on surfaces. A block diagram schematic, along with an image of the assembled breadboard system, is provided in Fig.…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…This system was based off a similar approach to that previously reported in the literature for discrimination of different gas phase chemicals. 18,19 A significant difference between previously reported results and the current work is that this work is focused on evaluating the capability of the human-color vision-based IR filter approach to discriminate between different solid explosives on surfaces. A block diagram schematic, along with an image of the assembled breadboard system, is provided in Fig.…”
Section: Methodsmentioning
confidence: 85%
“…These calculated vector coordinates correlate with experimental results obtained from the laboratory optical breadboard. 18 Two sets of CDSD analyses were conducted; the first used a surface concentration of 100 µg/cm 2 for each explosive (RDX, PETN, and HMX) as the training data, and the second used an RDX sample with 500 µg/cm 2 and 100 µg/cm 2 PETN and HMX samples as training data. This allowed for the evaluation of CDSD analysis to discriminate RDX from PETN and HMX using a mixture of α-, and β-RDX (100 µg/cm 2 RDX sample) and α-RDX (500 µg/cm 2 sample) as training data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sub-section describes the operating principle and the modelling procedures of the sensing component used in this work. It is inspired by the biomimetic design which previously has been demonstrated successfully for chemical [18][19][20] and biological sample [21] detection. The biomimetic sensor mimics the operation of the human eyes, which are capable of discriminating over 100,000 shades of (visible) colour over an environmental background despite being equipped with only three main types of cone cells [22,23].…”
Section: Biomimetic Sensor Systemmentioning
confidence: 99%
“…Research on colour sensitivity of mantis shrimp (Haptosquilla trispinosa), which has 12 different types of photosensitive cell covering different light wavelengths and polarisations, however, found that higher number of unique photoreceptors does not mean an improvement in colour discimination [25]; Mantis's spectral discrimination Δ𝜆 is in the region of 15 to 25 nm in comparison to humans' which is in the region of 1 to 8 nm [25,26] over the visible light region. In [18][19][20][21], a trichromat, three-colour, biomimetic sensor has been constructed in the mid-infrared range of light and a multi-variate statistics tool based on a patented comparative-discrimination spectral detection (CDSD) technique [20,27] has been used to perform the vectorial signal processing. In the present work, we have adopted a biomimetic sensor with a similar trichromat architecture, but the EORC is used for signal processing.…”
Section: Biomimetic Sensor Systemmentioning
confidence: 99%